Protocolo terapéutico empírico de la neumonía nosocomial - Vázquez, E. García (Medicine (Madr), 2014)
Nosocomial pneumonia is one of the most common infections in hospitalized patients and is associated with high morbidity and mortality. The treatment for these patients is established empirically and should be administered as soon as possible to improve their clinical prognosis. In most cases, microbiological documentation of the pneumonia's etiology is not achieved. There is therefore a well-established need for clear action protocols directed to all medical professionals who are in charge of caring for these patients.